2018
DOI: 10.1007/s10620-018-5305-z
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Butyrate Enhances Intestinal Riboflavin Uptake via Induction of Expression of Riboflavin Transporter-3 (RFVT3)

Abstract: Background: Uptake of riboflavin (RF) by intestinal epithelial cells occurs via a specific carrier-mediated process that involves the apically localized RF transporter-3 (RFVT3). Previous studies have shown that sodium butyrate (NaB) affects intestinal uptake of other substrates and expression of their membrane transporters, but its effect on intestinal uptake of RF and expression of RFVT3 has not been examined. Aims: To investigate the effect of NaB on intestinal RF uptake process and expression of the RFVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…VB2 is produced by several bacteria, including Lactobacillus, in the gut [43] and hosts express the VB2 transporter in the distal gut [44][45][46][47][48][49]. However, only estimates of VB2 that could be produced and supplied from the gut microbiota to the host are available [50].…”
Section: Discussionmentioning
confidence: 99%
“…VB2 is produced by several bacteria, including Lactobacillus, in the gut [43] and hosts express the VB2 transporter in the distal gut [44][45][46][47][48][49]. However, only estimates of VB2 that could be produced and supplied from the gut microbiota to the host are available [50].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that butyrate enhances intestinal B2 uptake demonstrating the crosstalk between host and microbiota in B2 metabolism. [ 47 ]…”
Section: Vitaminsmentioning
confidence: 99%
“…Interestingly, a recent study showed that butyrate enhances intestinal B2 uptake demonstrating the crosstalk between host and microbiota in B2 metabolism. [47] The anti-inflammatory and anti-oxidant potential of B2 and B2producing bacteria was demonstrated in a rodent model for acute colitis. [48] A prospective clinical intervention study in 70 CD patients showed also a clinical improvement, reduction in oxidative stress and several anti-inflammatory effects after 3 weeks of high oral B2 supplementation corresponding to about 100fold RDA, with minimal effects on the composition of the fecal microbiota.…”
Section: Vitamin B2-riboflavinmentioning
confidence: 99%
“…Recently, using Caco-2 cells and mouse colonoids, sodium butyrate (NaB) has been demonstrated to up-regulate intestinal Rf uptake inducing the expression of SLC52A3 , possibly due to epigenetics alteration in SLC52A3 promoter after NaB treatment [ 55 ]. Besides its important role as an energetic substrate in intestinal epithelial cells, butyrate is involved in the regulation of immune cell by modulating different processes of intestinal epithelial cells and leukocytes through the activation of G protein-coupled receptors and the modulation of the activity of enzymes and transcription factors including the histone deacetylase [ 56 ].…”
Section: Rf Transportersmentioning
confidence: 99%
“…mRFVT3 is the orthologue of hRFVT3 [ 190 ] and it has been shown to be the main transporter involved in carrier-mediated RF uptake in the native mouse small and large intestine [ 191 ]. Experiments performed on mouse colonoids demonstrated that mRFVT3 is up-regulated both at transcript and protein level after NaB treatment [ 55 ]. Further, it has been shown to be essential for mouse development, with Slc52a3 deficiency resulting in early embryonic lethality associated with defects in placental formation, but dispensable for neural differentiation and short-term maintenance [ 190 ], suggesting that in BVVLS patients with mutations in RFVT3 alternative transporters may act during embryogenesis to allow full-term development.…”
Section: Model Organisms To Study Flavin Homeostasis Alterationsmentioning
confidence: 99%